2020
DOI: 10.1007/s40858-020-00370-9
|View full text |Cite
|
Sign up to set email alerts
|

Following the effects of micronutrient supply in HLB-infected trees: plant responses and ‘Candidatus Liberibacter asiaticus’ acquisition by the Asian citrus psyllid

Abstract: Despite efforts of research to establish best nutrient management practices in HLB-affected citrus orchards, there are still doubts about the contribution of such strategies to minimizing losses caused by the disease in the citrus industry. We evaluated the effects of micronutrient (Zn, Mn, and/or Cu) supply and 'Candidatus Liberibacter asiaticus' (CLas) infection on physiological and growth traits of sweet orange trees (Citrus sinensis (L.) Osbeck)) to understand if enhanced micronutrient supply would improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…We propose collecting 30 to 60 whole citrus leaves (including petioles) for extracting enough sap for one sample-suggesting no more than three leaves per tree-and a separate analysis of each sample. This coincides with the methodology used by [57] and [58], who took 40 leaves when working with sweet orange (Citrus sinensis) cultivars.…”
Section: Type Of Tissuesupporting
confidence: 78%
See 3 more Smart Citations
“…We propose collecting 30 to 60 whole citrus leaves (including petioles) for extracting enough sap for one sample-suggesting no more than three leaves per tree-and a separate analysis of each sample. This coincides with the methodology used by [57] and [58], who took 40 leaves when working with sweet orange (Citrus sinensis) cultivars.…”
Section: Type Of Tissuesupporting
confidence: 78%
“…Instead of using petioles, in [55] and [56], the leaf blade midribs were used for sap analysis in broccoli (Brassica oleracea) and sugar cane (Saccharum officinarum), respectively, while in [52], the use of leaf blade vs. petioles was compared for sap analysis in strawberries (Fragaria × ananassa). In [57][58][59], leaf blades for sap analysis was recommended, which is becoming an interesting adaptation of the method by private companies in the Netherlands [19].…”
Section: Type Of Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Zambon et al [46] reported beneficial effects of Mn foliar application with three times higher than the recommended dose in HLB-affected trees have shown reduction of CLas titer and improvement of fruit production [46,47]. Therefore, it can be proven that nutrients have great importance in the interaction of the plant host, microbial community and vectors [14,46,48]. Most of essential nutrients influenced the severity of plant disease [49].…”
Section: Discussionmentioning
confidence: 99%